2019
DOI: 10.1128/jvi.00980-19
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Specific CD8 T Cells Selectively Infiltrate the Brain in Multiple Sclerosis and Interact Locally with Virus-Infected Cells: Clue for a Virus-Driven Immunopathological Mechanism

Abstract: EBV establishes a lifelong and asymptomatic infection in most individuals and more rarely causes infectious mononucleosis and malignancies, like lymphomas. The virus is also strongly associated with MS, a chronic neuroinflammatory disease with unknown etiology. Infectious mononucleosis increases the risk of developing MS, and immune reactivity toward EBV is higher in persons with MS, indicating inadequate control of the virus. Previous studies have suggested that persistent EBV infection in the CNS stimulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 81 publications
(178 reference statements)
3
67
0
Order By: Relevance
“…Activated CD8 T cells produce several other soluble mediators that can cause direct injury to oligodendrocytes and neurons or prevent remyelination, including TNF (Agresti et al, 1996;Denic et al, 2013;Magliozzi et al, 2019) and lytic enzymes, in particular granzyme B (Haile et al, 2011). A local, deleterious "cytokine storm" and ongoing cytotoxic activity are both compatible with the concept that CD8+ T cells recruited to the MS brain might be activated by a persistent EBV infection in the CNS, more specifically by EBV-infected B cells accumulating in the CNS connectival spaces (Serafini et al, 2007(Serafini et al, , 2019Veroni et al, 2018). Accordingly, EBV elicits very strong CD8 T cell responses that cause significant collateral tissue damage in EBV-associated immunopathologic diseases (Taylor et al, 2015).…”
Section: Discussionmentioning
confidence: 77%
“…Activated CD8 T cells produce several other soluble mediators that can cause direct injury to oligodendrocytes and neurons or prevent remyelination, including TNF (Agresti et al, 1996;Denic et al, 2013;Magliozzi et al, 2019) and lytic enzymes, in particular granzyme B (Haile et al, 2011). A local, deleterious "cytokine storm" and ongoing cytotoxic activity are both compatible with the concept that CD8+ T cells recruited to the MS brain might be activated by a persistent EBV infection in the CNS, more specifically by EBV-infected B cells accumulating in the CNS connectival spaces (Serafini et al, 2007(Serafini et al, , 2019Veroni et al, 2018). Accordingly, EBV elicits very strong CD8 T cell responses that cause significant collateral tissue damage in EBV-associated immunopathologic diseases (Taylor et al, 2015).…”
Section: Discussionmentioning
confidence: 77%
“…In this study, we did not measure markers of EBV reactivation, but we and others have shown that CD8 + EBV-specific T cells are present in active brain lesions of patients with MS, where antigens of the lytic activity are also detected. 10,16 Thus, it is conceivable that during disease activity, EBV reactivation is taking place, finding a weakened and senescent antigenspecific T-cell population, which is unable to contrast the viral infection. Functional data showed that EBV-specific T cells from untreated patients display signs of exhaustion and senescence, with low IFNγ production and reduced cytotoxic degranulation compared with healthy donors, whereas B cells on the contrary are significantly activated.…”
Section: Discussionmentioning
confidence: 99%
“…Mice studies have demonstrated that adoptive transfer of latent EBV antigen-specific CD8 + T-cells (either towards BMLF1 or LMP2) can reduce the blood viremia and target lyrically-replicating EBV-transformed B-cells [60]. Furthermore, a histopathological study showed significant infiltration of MS lesions with cytotoxic CD8 + T-cells that can recognize latent and lytic EBV proteins [61,62]. In spite of concerns regarding the risk of allogenic viral-specific T-cells to recognize recipient HLA molecules, the use of adaptive transfer has generally not resulted in graft-versus-host disease [63].…”
Section: Ebv Phase Antigen/gene Functionmentioning
confidence: 99%